2014
DOI: 10.1038/ncomms4955
|View full text |Cite
|
Sign up to set email alerts
|

An experimental limit on the charge of antihydrogen

Abstract: The properties of antihydrogen are expected to be identical to those of hydrogen, and any differences would constitute a profound challenge to the fundamental theories of physics. The most commonly discussed antiatom-based tests of these theories are searches for antihydrogen-hydrogen spectral differences (tests of CPT (charge-parity-time) invariance) or gravitational differences (tests of the weak equivalence principle). Here we, the ALPHA Collaboration, report a different and somewhat unusual test of CPT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…This feat was later repeated [7][8][9] , and in 2010 antihydrogen was successfully trapped 3 to facilitate its study. It was subsequently shown that antiatoms could be held 4 for up to 1,000 s, and various measurements have been performed on antihydrogen in the context of tests of CPT symmetry [10][11][12] or gravitational studies 13 .…”
mentioning
confidence: 99%
“…This feat was later repeated [7][8][9] , and in 2010 antihydrogen was successfully trapped 3 to facilitate its study. It was subsequently shown that antiatoms could be held 4 for up to 1,000 s, and various measurements have been performed on antihydrogen in the context of tests of CPT symmetry [10][11][12] or gravitational studies 13 .…”
mentioning
confidence: 99%
“…For example, the ALPHA external solenoid is not precisely fixed with respect to the magnetic trap, and B sol could be tilted with respect to the trap axis. This tilt is less than 2 mrad in the ALPHA system [23]. Figure 15(a) shows that such tilts increase the mixing fraction, but that the effect is small.…”
Section: Error Fieldsmentioning
confidence: 92%
“…Most of the antiatoms with energy above the trapping depth escape quickly, but simulations find that a few 'quasi-bound' antiatoms are slow to find an energetically-allowed escape 'hole', and remain trapped for substantial periods of time [21,22]. Some aspects of this choice of distribution have been validated by comparing simulation and experimental results [3,18,22,23].…”
Section: Simulationsmentioning
confidence: 99%
“…Recent years have seen major experimental advances in the production and trapping of antihydrogen,H , the positron (e + )−antiproton (p) bound state (see e.g., the reviews [1][2][3][4]), which have facilitated the first determinations of some of its properties [5][6][7][8][9]. Indeed, such measurements were only feasible due to the capability to hold ground stateH in a magnetic minimum neutral atom trap for periods of many minutes [10][11][12] to allow interaction with applied electric fields, or microwave or laser radiation.…”
Section: Introductionmentioning
confidence: 99%